Identification of Accessory Spleens During Laparoscopic Splenectomy Is Superior to Preoperative Computed Tomography for Detection of Accessory Spleens - Koshenkov, Vadim P. (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND: Missed accessory spleen (AcS) can cause recurrence of hematologic disease after splenectomy. The objective of the study was to determine whether detection of AcS is more accurate with preoperative computed tomography (CT) scan or with exploration during laparoscopic splenectomy. METHODS: A retrospective chart review was performed for 75 adult patients who underwent laparoscopic splenectomy for various hematologic disorders from 1999 to 2009. Preoperative CT scans were performed in all patients. Patients were followed for recurrence of disease, and a scintigraphy scan was performed in those with suspected missed AcS. RESULTS: The most common diagnosis was idiopathic thrombocytopenic purpura in 29 patients (39%), followed by non-Hodgkin's lymphoma in 22 patients (29%). Sixteen AcSs were found during surgery in 15 patients (20%), and preoperative CT scan identified 2 of these. Twelve AcSs were located at the splenic hilum (75%). Nine patients experienced recurrence of their disease, and none had a missed AcS on subsequent scintigraphy. Sensitivity of exploratory laparoscopy for detection of AcS was 100%, and for preoperative CT scan was 12.5% (P = .005). CONCLUSION: Exploratory laparoscopy during splenectomy is more accurate than preoperative imaging with CT scan for detection of AcS. Preoperative CT scan misses AcS frequently and should not be obtained for the purpose of its identification.